Weak Electrostatic Interaction Enabled Highly Oriented Assembly of Gold Nanorods onto Ultrathin Flagella Bionanofibers. Issue 7 (24th May 2021) - Qiu, Penghe; Wang, Lin; Li, Yan; Mao, Chuanbin
Abstract : Biological substrates are generally considered unfavored for electrostatic uptake of nanoparticles due to their low surface charges. Herein, the electrostatic interaction between weakly charged ultrathin flagella bionanofibers and gold nanorods (AuNRs) is investigated. It is discovered that compared with the reported AuNRs assembly onto one‐dimensional (1D) templates of strong charges, the weak electrostatic interaction here can generate more ordered 1D AuNRs array. Under strong attraction force, AuNRs can bind firmly on templates by either narrow heads or long sidewalls, resulting in less ordered 1D structure. While under weak attraction force, AuNRs can be captured only if interacting with flagella using their long sidewalls to obtain accumulative strong enough force. Another discovery is that under weak AuNRs–flagella electrostatic attraction force, the relatively stronger AuNRs–AuNRs repulsion force plays a significant role in determining the interparticle gap and the single‐ or double‐string pattern of AuNRs on ultrathin flagella. Advantage is also taken of the bio‐origin of flagella by assembling AuNRs onto flagella that are still attached to living bacterium. Such a capability makes our approach highly feasible for potential device fabrication, as individual nanoarray is hard to manipulate, but would be greatly facilitated if it is associated with a micron‐sized base, like bacteria. Abstract : Weak electrostatic attraction force can assemble gold nanorods (AuNRs) into highly oriented arrays along ultranarrow flagella nanofibers. The inter‐AuNRs repulsion force determines not only the spacing, but also the single‐ and double‐string pattern of AuNRs. The capability of assembling AuNRs on the flagella of living bacteria allows facile transportation of the structures to desired spots toward potential device fabrication.